2018
DOI: 10.1111/sltb.12471
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Suicidality in Adolescents with Major Depression: Resting‐State Functional Connectivity of the Precuneus and Posterior Cingulate Cortex

Abstract: Findings of hyperconnectivity stemming from the precuneus and hypoconnectivity from the PCC may reflect maladaptive self-reflection and mentalization. However, additional investigation is warranted to further clarify these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…Our results also indicate that the most important regions that help to discriminate BD and MDD are middle temporal gyrus, insula, precuneus, putamen, superior parietal gyrus, and inferior occipital gyrus. The abnormalities in these regions have been widely reported in MDD ( Wang et al, 2012 , Peng et al, 2015 , Schreiner et al, 2019 ) or BD ( Favre et al, 2014 ) literature. Our results argue that although these regions shows atypical patterns in both MDD and BD, their abnormalities may pertain to the different pathophysiology of mood disorders and may be particularly helpful for separating patients with challenging mood diagnoses.…”
Section: Discussionmentioning
confidence: 93%
“…Our results also indicate that the most important regions that help to discriminate BD and MDD are middle temporal gyrus, insula, precuneus, putamen, superior parietal gyrus, and inferior occipital gyrus. The abnormalities in these regions have been widely reported in MDD ( Wang et al, 2012 , Peng et al, 2015 , Schreiner et al, 2019 ) or BD ( Favre et al, 2014 ) literature. Our results argue that although these regions shows atypical patterns in both MDD and BD, their abnormalities may pertain to the different pathophysiology of mood disorders and may be particularly helpful for separating patients with challenging mood diagnoses.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, in one study resting-state fMRI in 40 adolescents with MDD, Ordaz and colleagues reported that reduced network coherence in central executive, default mode and salience networks was associated with most severe lifetime ideation (Ordaz et al ., 2018 ). Similarly, Schreiner and colleagues recently reported in a sample of 58 adolescents with MDD that higher self-reported suicidal symptoms were associated with resting-state hyperconnectivity between left precuneus and left primary motor cortex, left somatosensory cortices and middle and superior frontal gyri as well as hypoconnectivity between left posterior cingulate cortex and left cerebellum, lateral occipital cortex and temporal occipital fusiform gyrus (Schreiner et al ., 2018 ). In a task-based fMRI study, Miller et al .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Indeed, a small number of resting-state fMRI studies have documented nuanced alterations in the CEN, DMN, and SN in adolescents with history of suicide attempts, with SI, and with NSSI (for a review, see 11). In depressed adolescents, greater severity of SI has been associated with both greater connectivity between one node of the DMN (precuneus) with sensorimotor regions, as well as lower connectivity between another node of the DMN (PCC) with visual attention regions 23 . In another sample of depressed adolescents, researchers documented lower network coherence (i.e., within-network connectivity) of the anterior node of the DMN (medial PFC), SN (centered on the dACC) oxford, and left CEN 24 in relation to participants’ most severe intensity of SI in the lifetime; further, longitudinal increases in network coherence of the SN (centered on the dACC) in this same sample were also associated with decreases in severity of SI 25 .…”
Section: Introductionmentioning
confidence: 99%